A Review Study on Efficacy of Immunomodulatory agents used for the Treatment of Covid-19 - Kurya, Abdulaziz Umar; Toro, Abdulhakim Umar; Bello, Usman Rabiu; Sharma, Dinesh Chandra (Asian Journal of Biological and Life Sciences, 2020)
The infection started at December, 2019 with the random elevation of respiratory tract disorders at Wuhan hospital in China. Sequencing of lower respiratory tract samples by independent laboratories in China identified a novel corona virus distinct from the other Severe Acute respiratory Syndrome (SARS) strains of coronavirus previously known to infect humans, which was earlier named as Corona Virus Disease 2019 (COVID-19) by the world health organization. The present review work highlighted the outbreaks of COVID-19 on the basis of scientific journals published in the reputed research articles and other authentic sources. Increased morbidity and mortality rate in COVID-19 is largely associated with Acute Respiratory Distress Syndrome (ARDS). Throughout the period of Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) infections and SARS CoV-2, Elevated level of proinflammatory cytokines and chemokine was commonly observed in patients requiring Intensive Care Unit (ICU) admission as compared to those in which the infection was less severe and did not require ICU admission due to excessive immune responses induced by the immune system. Potential of immunomodulatory agents such as Interleukin- 1 (IL-1) and Interleukin-6 (IL-6) receptor antagonist, Tumor Necrosis Factor- α (TNF- α) blockers and corticosteroids in treatment of COVID-19 declared urgent need for clinical researches to precisely confirm the effectiveness and safety of the therapeutics.
Keywords: Corona Viruses and Immunotherapyy; Covid-19; Cytokines; SARS-CoV-2